Pharmacokinetic herb-drug interactions: Altered systemic exposure and tissue distribution of ciprofloxacin, a substrate of multiple transporters, after combined treatment with Polygonum capitatum Buch.-Ham. ex D. Don extracts - Li, Ziqiang; Du, Xi; Tian, Shuang; Fan, Shanshan; Zuo, Xurui; Li, Yanfen; Wang, Ruihua; Wang, Baohe; Huang, Yuhong (Frontiers in Pharmacology, 2022)
Background: Combination of Polygonum capitatum Buch.-Ham. ex D. Don extract (PCE) and ciprofloxacin (CIP) was commonly prescribed in the treatment of urinary tract infections. Their pharmacokinetic herb-drug interactions (HDIs) were focused in this study to assess potential impact on the safety and effectiveness. Methods: A randomized, three-period, crossover trial was designed to study the pharmacokinetic HDI between PCE and CIP in healthy humans. Their pharmacokinetic- and tissue distribution-based HDIs were also evaluated in rats. Gallic acid (GA) and protocatechuic acid (PCA) were chosen as PK-markers of PCE in humans and rats. Potential drug interaction mechanisms were revealed by assessing the effects of PCE on the activity and expression of multiple transporters, including OAT1/3, OCT2, MDR1, and BCRP. Results: Concurrent use of PCE substantially reduced circulating CIP (approximately 40%–50%) in humans and rats, while CIP hardly changed circulating GA and PCA. PCE significantly increased the tissue distribution of CIP in the prostate and testis of rats, but decreased in liver and lungs. Meanwhile, CIP significantly increased the tissue distribution of GA or PCA in the prostate and testis of rats, but decreased in kidney and heart. In the transporter-mediated in vitro HDI, GA and PCA presented inhibitory effects on OAT1/3 and inductive effects on MDR1 and BCRP. Conclusion: Multiple transporter-mediated HDI contributes to effects of PCE on the reduced systemic exposure and altered tissue distribution of CIP. More attention should be paid on the potential for PCE-perpetrated interactions.